Analisis Pengaruh Sikap Komputer Dan Kegunaan Persepsian Terhadap Minat Perilaku Yang Dimoderasi Oleh Perbedaan Gender - I Putu Sugiartha Sanjaya (Universitas Airlangga, 2008)
The objective of this study is to investigate whether computer attitude influences perceived usefulness. This study also investigates whether gender influence relation between perceived usefulness and behavioral intention. The subject of this study is student from five private universities in Daerah Istimewa Yogyakarta. There are 364 respondents. The result of this study supports hypothesis of this study that computer attitude influences perceived usefulness. This study also supports hypothesis that gender influence relation between perceived usefulness and behavioral intention.